The Legal Analysis of Age Limitations of Child Victims on Criminal Actions in Justice Perspective - Sri Tatmala Wahanani; Ira Alia Maerani; Siti Ummu Adillah (Law Development Journal, 2022)
The purpose of this study was to determine and analyze the impact of changes in the age limit of child victims, provisions for the age limit of child victims in Islamic law and age limits for victims of crimes of decency with justice. The approach method in this study uses a doctrinal research method (juridical normative) and a legal psychological approach method, with a descriptive analytical research specification. In collecting data used literature study method with qualitative data analysis. From the results of the study, it was concluded that the change in the age limit of child victims in positive law in Indonesia in 2002 from 15 (fifteen) to 18 (eighteen) years had an impact on increasing the number of cases of decency crimes. Even criminal acts of decency are dominated on the basis of reports from the parents of the victim's child who do not approve of the courtship (consensual) relationship between the victim's child and the perpetrator of the crime of decency. This has implications for the conscience of justice for law enforcement officers to demand or make decisions against the perpetrators, there is a sense of injustice, there is a sense of inadequacy when they have to demand or impose punishment, because actually the crime was also desired by the victim. So for the sake of realizing justice, the age of the child victim of 18 (eighteen) years needs to be reconsidered for revision or change.